2016
DOI: 10.1080/01490451.2015.1059523
|View full text |Cite
|
Sign up to set email alerts
|

Winter Planktonic Microbial Communities in Highland Aquatic Habitats

Abstract: +36-1-381-2178 2 KEY WORDS: peat bog lake, saline lake, crater lake, sulphuric bubbling pool, winter plankton RUNNING TITLE: Winter plankton of highland aquatic habitats 3 AbstractWinter conditions in aquatic habitats of the temperate zone markedly differ from those present in warmer seasons, nevertheless, relatively scarce information is available on planktonic microbial composition, as sites are not easily accessible and it was supposed traditionally that microbial activity is low during this cold period. Si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 60 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…The densities of microorganisms in brines were relatively high on average 10 7 cells/mL. They were similar to those detected in the solar salterns throughout the world (Oren et al 1996 ; Antón et al 2000 ; Burns et al 2004 ; Trigui et al 2011 ; Máthé et al 2014 ; Andrei et al 2015 ; Gomariz et al 2015 ; Felföldi et al 2016 ; Çinar and Mutlu 2016 ). Hypersaline environments of greater abundance of microorganisms (more than 10 8 cells/mL) are also known (Guixa-Boixareu et al 1996 ; Ochsenreiter et al 2002 ).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The densities of microorganisms in brines were relatively high on average 10 7 cells/mL. They were similar to those detected in the solar salterns throughout the world (Oren et al 1996 ; Antón et al 2000 ; Burns et al 2004 ; Trigui et al 2011 ; Máthé et al 2014 ; Andrei et al 2015 ; Gomariz et al 2015 ; Felföldi et al 2016 ; Çinar and Mutlu 2016 ). Hypersaline environments of greater abundance of microorganisms (more than 10 8 cells/mL) are also known (Guixa-Boixareu et al 1996 ; Ochsenreiter et al 2002 ).…”
Section: Discussionsupporting
confidence: 75%
“…The influence of salinity on bacterial and archaeal community composition in saline systems with rapid changes in salinity such as estuaries (Campbell and Kirchman 2013 ; Crump et al 2004 ; Moss et al 2006 ), soda pans (Szabó et al 2017 ), and coastal solar salterns (Casamayor et al 2002 ; Dillon et al 2013 ), as well as in habitats with stable salinity conditions, characterized by a slow evolution from freshwater to saline (Felföldi et al 2016 ; Máthé et al 2014 ; Wu et al 2006 ; Xing et al 2009 ) has been investigated. These studies have definitively shown that salinity is one of the major factors controlling microbial abundance and diversity.…”
Section: Introductionmentioning
confidence: 99%
“…Basic physicochemical parameters were determined on site using a MultiLine P 8211 multimeter (WTW). Chemical analyses were performed under laboratory conditions according to the methods described in detail in Felföldi et al ( 2016 ).…”
Section: Methodsmentioning
confidence: 99%
“…For pigment analyses, the samples were filtered through a GF-5 glass fiber filter (Whatman). Chlorophyll a (Chl a ) and bacteriochlorophyll a (Bchl a ) were extracted from the filters as described in Felföldi et al ( 2016 ), while another filter set per se was used for in vivo absorption measurements. Chlorophyll concentration was measured using the method of Wellburn ( 1994 ), and the concentration of Bchl a was determined according to Biel ( 1986 ).…”
Section: Methodsmentioning
confidence: 99%
“…To achieve this, growth tests were performed using media with different salt concentration values and ionic compositions on bacterial strains that were isolated from three sets of saline lakes that differed in ionic composition (Fig. 1 ): (1) two soda lakes located in Kiskunság (Hungary, Central Europe), characterized by high sodium hydrogen carbonate content (Boros et al 2014 ); (2) two soda lakes in Vojvodina (Serbia, Central/Southeast Europe) with approximately equal proportion of sodium hydrogen carbonate, sodium chloride and sodium sulfate (Boros et al 2014 ); and (3) two Transylvanian saline lakes (Romania, Eastern Europe), which are dominated by sodium chloride (Borsodi et al 2013 ; Máthé et al 2014 ; Andrei et al 2015 ; Felföldi et al 2016 ).
Fig.
…”
Section: Introductionmentioning
confidence: 99%